Мефодий Буслаев. Лед и пламя Тартара: [повесть] / Дмитрий Емец ; художник И. Варавин - Емец Дмитрий Александрович (Мефодий Буслаев, 2013)
Экземпляры: ДБ (20151118) / Инвентарный номер: 44179 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Е 60 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6